Effect of Flipped Classroom on Improving Independence and Learning Achievement in Social Studies in Junior High School - Elpisah Elpisah; Devilla, Rego; Suarlin Suarlin; Madiana Madiana (International Journal of Educational Development, 2026)
This study investigates (1) the impact of the Flipped Classroom model on students’ learning independence in Social Studies, (2) its effect on Social Studies achievement, and (3) its simultaneous influence on both variables among Grade VIII students at SMPN 10 Satap Liukang Tangaya. A quantitative approach was applied using a quasi-experimental method with a Non-Equivalent Control Group Design. The sample comprised 33 students, with 17 assigned to the experimental class and 16 to the control class. Data collection instruments included a learning independence questionnaire, Social Studies achievement tests, observation sheets, and documentation. The data were analyzed through descriptive statistics, normality and homogeneity tests, paired samples t-tests, independent samples t-tests, and MANOVA using SPSS. The findings reveal that the Flipped Classroom model significantly enhances students’ learning independence, as evidenced by independent samples t-test results (Sig. < 0.05). It also significantly improves Social Studies learning outcomes, indicated by higher posttest scores in the experimental class compared to the control class (Sig. < 0.05). Furthermore, MANOVA results confirm a significant simultaneous effect on both learning independence and achievement (Sig. < 0.05). These results demonstrate that the Flipped Classroom model effectively improves the overall quality of Social Studies instruction for Grade VIII students.